Oxygen-coupled redox regulation of the skeletal muscle ryanodine receptor/Ca2+ release channel (RyR1): sites and nature of oxidative modification - Sun, Qi-An; Wang, Benlian; Miyagi, Masaru; Hess, Douglas T; Stamler, Jonathan S (The Journal of biological chemistry, 2013)
In mammalian skeletal muscle, Ca(2+) release from the sarcoplasmic reticulum (SR) through the ryanodine receptor/Ca(2+)-release channel RyR1 can be enhanced by S-oxidation or S-nitrosylation of separate Cys residues, which are allosterically linked. S-Oxidation of RyR1 is coupled to muscle oxygen tension (pO2) through O2-dependent production of hydrogen peroxide by SR-resident NADPH oxidase 4. In isolated SR (SR vesicles), an average of six to eight Cys thiols/RyR1 monomer are reversibly oxidized at high (21% O2) versus low pO2 (1% O2), but their identity among the 100 Cys residues/RyR1 monomer is unknown. Here we use isotope-coded affinity tag labeling and mass spectrometry (yielding 93% coverage of RyR1 Cys residues) to identify 13 Cys residues subject to pO2-coupled S-oxidation in SR vesicles. Eight additional Cys residues are oxidized at high versus low pO2 only when NADPH levels are supplemented to enhance NADPH oxidase 4 activity. pO2-sensitive Cys residues were largely non-overlapping with those identified previously as hyperreactive by administration of exogenous reagents (three of 21) or as S-nitrosylated. Cys residues subject to pO2-coupled oxidation are distributed widely within the cytoplasmic domain of RyR1 in multiple functional domains implicated in RyR1 activity-regulating interactions with the L-type Ca(2+) channel (dihydropyridine receptor) and FK506-binding protein 12 as well as in "hot spot" regions containing sites of mutation implicated in malignant hyperthermia and central core disease. pO2-coupled disulfide formation was identified, whereas neither S-glutathionylated nor sulfenamide-modified Cys residues were observed. Thus, physiological redox regulation of RyR1 by endogenously generated hydrogen peroxide is exerted through dynamic disulfide formation involving multiple Cys residues.